The role of protein elongation factor eEF1A2 in ovarian cancer - Lee, Jonathan M (BioMed Central, 2003)
Frequent gains of chromosome 20q12-13 in ovarian tumors indicate that at least one important oncogene is found at that locus. One of the genes there is EEF1A2, which maps to 20q13.3 and encodes protein elongation factor eEF1A2. This review will focus on recent evidence indicating that EEF1A2 is an important ovarian oncogene and that the protein elongation network can activate tumorigenesis and inhibit apoptosis.